CLINICOPATHOLOGICAL PROFILE AND MANAGEMENT OF SINONASAL MASSES IN A TERTIARY CARE TEACHING HOSPITAL (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Sinonasal masses comprise a wide range of inflammatory, benign, and malignant lesions that often present with similar symptoms. Accurate diagnosis is essential due to the proximity of the sinonasal region to vital structures. Objectives: To study the clinical presentation, pathological profile, radiological findings, and treatment outcomes of sinonasal masses. Materials and Methods: This prospective observational study was conducted in the Department of ENT, Kurnool Medical College after approval from the Institutional Ethics Committee (IEC No: KMC/IEC/2023-24/ENT/274). Patients with sinonasal masses underwent clinical evaluation, diagnostic nasal endoscopy, imaging, and histopathological examination. Data were analysed using descriptive statistics. Results: Eighty patients were included. Non-neoplastic lesions were most common (63.8%), followed by benign tumors (22.5%) and malignancies (13.7%). Nasal obstruction was the most frequent symptom. Inflammatory nasal polyps were the most common diagnosis. Functional endoscopic sinus surgery was the primary treatment in most patients. Conclusion: Sinonasal masses are predominantly inflammatory and benign. Early diagnosis using nasal endoscopy and imaging allows effective management, while malignant lesions require multimodality treatment.